2017
DOI: 10.1177/0954411916680235
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal head and torso vibration exposure during inter-hospital transfer

Abstract: Inter-hospital transport of premature infants is increasingly common, given the centralisation of neonatal intensive care. However, it is known to be associated with anomalously increased morbidity, most notably brain injury, and with increased mortality from multifactorial causes. Surprisingly, there have been relatively few previous studies investigating the levels of mechanical shock and vibration hazard present during this vehicular transport pathway. Using a custom inertial datalogger, and analysis softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
4
15
0
Order By: Relevance
“…The rate of severe brain injury was not significantly higher in non-transferred infants who remained in non-tertiary neonatal hospitals compared with controls. This finding has two possible explanations: these infants might have died before severe brain injury was detected, as mortality was higher in this group, or there may be a mechanistic link between early postnatal transfer and brain injury related to physiological instability or vibration injury during transport 51…”
Section: Discussionmentioning
confidence: 87%
“…The rate of severe brain injury was not significantly higher in non-transferred infants who remained in non-tertiary neonatal hospitals compared with controls. This finding has two possible explanations: these infants might have died before severe brain injury was detected, as mortality was higher in this group, or there may be a mechanistic link between early postnatal transfer and brain injury related to physiological instability or vibration injury during transport 51…”
Section: Discussionmentioning
confidence: 87%
“…During neonatal transport, WBV often exceeds the recommended level deemed safe for adults with the head of the infant appearing to be at greatest risk . Excessive exposure in adults can cause ill effects including musculoskeletal and neurovascular injury .…”
Section: Key Environmental Exposures During Inter‐hospital Transportmentioning
confidence: 99%
“…Vibration and linear acceleration experienced during the transfer process may lead to fluctuations in CBF and be the key mechanism for IVH in preterm infants and although causation is challenging to demonstrate it is supported by animal models . Attempts to reduce WBV exposure with the use of different mattresses, including gel materials, have not demonstrated effective attenuation of WBV, especially in infants at high risk of IVH . Innovations are needed to significantly reduce WBV during neonatal transport which can then be studied in appropriately powered clinical trials.…”
Section: Key Environmental Exposures During Inter‐hospital Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to non-transported premature infants, transported babies have more severe brain injury [1], [2], [3]. While the reasons for this are not fully understood, studies have shown that both vibration and noise are at excessive and potentially harmful levels inside ambulances [4], [5], [6], [7]. A reduction in these environmental stressors could improve outcomes.…”
Section: Introductionmentioning
confidence: 99%